The Effect of Leadership on the Performance of Village Apparatus and Community Institutions at the Cibenda Village Office, Ciemas District, Sukabumi Regency - Udriyah; Apriyanti; Dwi Rachmawati (Neo Journal of economy and social humanities, 2022)
One of the things that must be considered in the implementation of work is the realization of good employee performance. Therefore employee performance needs to be considered in an effort to achieve maximum goals, this shows that leadership has a very important role in achieving employee performance, and leaders are able to apply appropriate leadership and in accordance with existing situations and conditions, so employees will also can work comfortably and with high enthusiasm, this work assessment is carried out to assess and is also used to evaluate abilities, skills, assess achievement and reassess the growth of each employee. If this performance appraisal is done properly it can be used to increase loyalty and motivation for the employees.